Three-dimensional Analysis of Electromagnetic Nanomaterial Flow and Thermal Variations for Forced Convection - Yadav, Sweeti; P. A. Dinesh,; K. R. Roopa,; Gogate, S. Shashi Prabha (Journal of Mines, Metals and Fuels, 2023)
This paper investigates the three-dimensional motion of electromagnetic nanofluid under the influence of heat source/sink, nonlinear heat radiation, magnetic field, and altered Arrhenius equation. Nonlinear stretching in the velocity is considered in the x-direction. Thermophoresis (Nt) and Brownian motion (Nb) are also considered in nanoparticle concentration profiles and temperature analysis. The boundary layer equations are transformed into nonlinear ODEs using suitable similarity transformations. The coupled nonlinear homogeneous system of ordinary differential equations is tackled by the MAPLE software. Non-dimensional system of the equation contains fourteen physical parameters Fr, Nb, M, γ, λ, Rd, δ, Pr, Nt, S, E, Sc, Bi and power index, which are governed by the physical model. Graphs are presented to show the impact of the abovementioned parameters on temperature, concentration and velocity profile. The present study contributes by observing how the aforementioned parameters influence the heat dissipation rate of nanofluids. This study has broad applications in the field of nanofluids like oil production, metal extrusion, heat exchangers, catalytic reactors etc. Also, results for a particular case found good concurrence with earlier work.